L’objectivité du document en classe d’histoire : un obstacle à dépasser pour être compétent - Lucie Gomes (Recherches en Éducation)
To study documents in history class is a common practice. However, the skills to be able to study them in history are general. We identified a skill to build a problem from classroom documents. Our experiments have led us to observe an important obstacle to the acquisition of this skill: students wonder if the document is objective. We will see what this remote out of the epistemology of historians implies.